Avaliação in vitro dos fatores de patogenicidade de Candida spp sob a ação da Terapia Fotodinâmica - Dias, Isabella Jardelino (2017)
The present study aimhed to analyze, in vitro, the effect of Photodynamic Therapy, using methylene blue as a photosensitizer, on the main pathogenicity factors of Candida spp. The same consisted of an experimental study with direct observation on the antibiofilm activity, expressed in CFU/mL and by cell viability, besides the morphological analysis, through the test of adhesion to abiotic substrates and presence of chitin in the cell wall. From the suspension of Candida albicans and tropicalis, clinical and standard strains, mature biofilms were prepared. The light source used was the InGaAlP laser, with a wavelength of 660 nm and a total dose of 178.5 J / cm². The following groups were established in the study: (1) laser irradiated; (2) in the presence of methylene blue for 20 minutes; (3) Photodynamic Therapy with 20 minute pre-irradiation; (4) positive control (Nystatin); (5) growth control. The antibiofilm activity was analyzed by ANOVA-one way test and Tukey's test with significance level of 5%. The efficacy of TDF was expressed as one of the lowest values obtained in CFU / mL (p <0.05), as well as rupture of yeast reproductive cycle, reduction in fungal cell number and volume, induction of morphological transition, cell integrity and impairment of the fungal regenerative cycle. Therefore, it has concluded that the effectiveness shown by Photodynamic Therapy in the pathogenicity factors of Candida ratifies consolidated clinical concepts, thus elucidating the specific mechanisms that the treatment has for this purpose.